Discounting and environmental policy - Scheraga, Joel D. (Routledge revivals., 2018)
"This book was published in 2003. The "International Library of Environmental Economics and Policy" explores the influence of economics on the development of environmental and natural resource policy. In a series of 25 volumes, the most significant journal essays in key areas of contemporary environmental and resource policy are collected. Scholars who are recognized for their expertise and contribution to the literature in the various research areas serve as volume editors and write essays that provides the context for the collection. Volumes in the series reflect three broad strands of economic research including: natural and environmental resources; policy instruments and institutions; and methodology. The editors, in their introduction to each volume, provide a state-of-the-art overview of the topic and explain the influence and relevance of the collected papers on the development of policy. This reference series provides access to the economic literature that has shaped contemporary perspectives on land use analysis and policy."--Provided by publisher